Konsep Pendidikan sebagai Suatu Sistem dan Komponen Sistem Pendidikan - Sri Handayani; Agis Mulya Akbar; Namira Septia (Pusat Riset dan Inovasi Nasional, 2025)
Education is a complex and structured process that functions as part of a mutually supporting system. This article discusses education as a system and outlines the main components that make it up. Education is seen as a system consisting of interconnected elements, such as educational goals, students, educators, curriculum, facilities, learning methods, and environment. Each element has a complementary role to achieve educational goals optimally. This article also emphasizes the importance of synergy and balance between these components so that the education system can run effectively in various contexts, whether formal, non-formal or informal. With a systems-based approach, education is not only understood as a learning process, but also as a strategy for building competent and characterful individuals. This study provides conceptual guidance for practitioners and policy makers to design an education system that is flexible and able to face global challenges.